Studi Kasus pada Penderita Bipolar Disorder Menggunakan Pendekataan Model Keperawatan Stuart Stress Adaptation di Probolinggo - Wuryaningsih, Emi Wuri; Zuhro, Zuiffah Lailatul; S, Jon Hafan (Pustaka Kesehatan, 2023)
The problem that is often faced by people with bipolar disorder is that they cannot control the emotions and feelings they feel because they do not know the cause and also how to cope or respond when patients experience both episodes. The purpose of this study is to identify problems associated with predisposing and precipitation factors in order to get the right diagnosis. The research design used in this study is a case study. Predisposing factors include biological factors, loss of objects, personality, learning, and behavior. Precipitation factors in patients include loss, life events, roles, and physiology. Diagnosis The problem is based on complaints experienced by patients and those closest to them, anxiety and low self-esteem. The intervention that has been done by researchers to patients or participants for several weeks the patient is quite independent. Efforts can be made to improve the health quality of patients themselves by providing psychoeducation and nursing interventions. Humans are a denial of depression, individuals who experience mania are dominated by id with few manifestations of the super ego until the individual experiences a cycle back to the normal state or depressive phase of bipolar disorder.